Blockade of fear-induced antinociception with intra-amygdala infusion of midazolam: Influence of prior test experience - Baptista, Daniela [UNESP]; Bussadori, Karina; Nunes-de-Souza, Ricardo Luiz [UNESP]; Canto-de-Souza, Azair [UNESP] (Elsevier B.V., 2009)
Intra-amygdala infusion of midazolam, a benzodiazepine receptor agonist, produces anxiolytic-like effects in mice when first exposed to the elevated plus-maze (EPM) and blocks antinociception induced in mice confined in the open arm of the EPM. However, benzodiazepines fail to alter anxiety in maze-experienced rodents, a phenomenon defined as "one-trial tolerance" (OTT). The main purpose of the present study was to investigate whether intra-amygdala midazolam attenuates the open ann-induced antinociception (OAA) in maze-experienced mice. Nociception was assessed by the writhing test (intraperitoneal injection of 0.6% acetic acid). In Experiment 1, nociception was recorded in maze-experienced mice without prior drug treatment. Experiment 2 investigated the effects of systemic midazolam (0.5, 1.0 and 2.0 mg/kg, s.c.), injected before EPM trial 2, on OAA in maze-experienced mice. in Experiment 3, the effects on OAA of intra-amygdala midazolam (30 nmol/0.1 mu l), injected before trial 1 (maze-naive) or before trial 2 (maze-experienced), were observed. The effects on OAA of intra-amygdala midazolam injected before trial 1 and trial 2 were also investigated (Experiment 4). The results showed that OAA remained unchanged in maze-experienced mice and was insensitive to systemic midazolam. However, intra-amygdala midazolam attenuated OAA in maze-naive mice, but not in maze-experienced mice. Even when given before both trial 1 and trial 2, intra-amygdala midazolam failed to alter OAA in maze-experienced mice. Taken together, these results confirm that the GABA(A)/benzodiazepine receptor complex located within the amygdala plays a role in OAA in maze-naive mice. The lack of effects following systemic or intra-amygdala midazolam on OAA in maze-experienced mice suggests that the OTT is also observed in the modulation of nociception and that the GABA(A)/benzodiazepine receptor located within this limbic forebrain structure participates in this process. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Fear; Antinociception; Amygdala; Midazolam; Elevated plus-maze; Mice